Patient's experiences of diabetes care at a tertiary health facility in Lilongwe, Malawi - Ellen Nkambule; Kondwani Wella; Annie Msosa; Balwani Chingatichifwe Mbakaya; Evelyn Chilemba; Gladys Msiska (BMC, 2023)
Abstract Background Little is known about experiences of rural people with diabetes care at a tertiary health facility in low-income settings. Understanding their experiences is essential for developing effective diabetes care interventions. Methods The study employed a qualitative narrative inquiry. Participants were identified at a diabetes clinic at a tertiary-level healthcare facility. Ten participants from the rural areas attending the diabetes clinic were purposively selected. Data were collected through in-depth interviews in the privacy of the homes of the study participants and analysis was done using the Riessman approach to thematic narrative analysis. Results In this study, the following four themes emerged: (1) the long pathway to a diagnosis of diabetes; (2) Poverty-related hardships and diabetic clinic attendance; (3) The impact of health worker attitudes and behavior on diabetes care; and (4) Low resources and their impact on self-management. Conclusions Rural-based patients living with diabetes encounter enormous challenges as they access diabetes care. One of the challenges is delayed diagnosis of diabetes. There is a need to introduce point-of-care (POC) testing to improve diabetes diagnosis. In addition, there is a need to strengthen awareness campaigns among the population so that people are well informed about the signs and symptoms of diabetes to promote early diagnosis. Diabetes care must be decentralized from tertiary hospitals to primary health centers. This will improve access to diabetes care and reduce the burden associated with traveling a long distance to access diabetes care in Malawi.